A Very Rare Case of Coronary Artery Bypass Grafting in a Progeria Child - Cerejo, R (2021)
Hutchinson-Gilford progeria syndrome is a rare genetic disorder, characterized by progressive premature aging and early death in the first or second decade of life, usually secondary to cardiovascular events (myocardial infarction and stroke). We report a case of a 14-year-old boy with progeria syndrome and cardiac arrest due to myocardial infarction, who was submitted to an immediate coronary angiography which revealed left main stem and three-vessel coronary artery disease. A prompt double bypass coronary artery grafting surgery was performed, and, despite successful coronary reperfusion, the patient remained in coma and brain death was declared on fourth day after surgery.